CHEMICAL TRANSFORMATIONS OF THE CONDENSATION PRODUCTS OF PYRIDOXAL WITH L-Α-VALINE AND D-Α-VALINE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The kinetics and mechanism of the reactions of pyridoxal with L-α- and D-α- valine were studied. Under comparable conditions, the condensation of  L-α- and D-α- valine with pyridoxal includes three kinetically different steps. The first fast step is addition of the amino acid to pyridoxal with formation of the corresponding amino alcohol, the second (slower) step is dehydration of the amino alcohol to give Schiff base, and the third (very slow) step is elimination of α-hydrogen atom from the L-α-amino acid fragment or decarboxylation of the D-α-amino acid fragment, followed by isomerization of the Schiff base to quinoid structure whose subsequent hydrolysis yields pyridoxamine and pyruvic acid or acetaldehyde, respectively. A scheme was proposed for chemical transformations of the pyridoxal condensation products with L-α- and D-α- valine.
Keywords: Vitamins В6, Amino acids, Structure of amino acids and bases Schiff..